Membrane technology for microalgae harvesting - Leam, J.J. (Elsevier, 2019)
Biofuel production from microalgae has gained interest over the years because it offers better sustainability. As biofuel feedstock, microalgae undergo several processing steps, namely, cultivation, harvesting, extraction, and conversion. The harvesting step has been identified as the most energy-consuming step. Various methods have been identified for microalgae harvesting, and membrane technology is seen one of the most promising technology, thanks to its low-energy footprint. This chapter covers recent developments of membrane technology for microalgae harvesting. It includes material and system development as well as membrane fouling control for both the pressure-driven and the osmotically driven processes. Lastly, perspective on further research directions is also provided. Despite showing promises, pressure-driven membrane processes are highly limited by membrane fouling. Fouling control management through innovative membrane developments and dynamic system has recently been reported. Application of forward osmosis as the low fouling membrane process has been recently reported. However, it seems to be attractive only as a stand-alone process without draw solute recovery. Finally, it is recommended to perform a larger-scale test to accurately gauge membrane technology potential. Audit on energy footprint and technoeconomy of the processes is open for further assessments. Â© 2020 Elsevier Inc. All rights reserved.